2023
DOI: 10.2147/ijwh.s389939
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Child Marriage and Its Related Adverse Health Outcomes Among Married Women in Sub-Region of Serejeka, Central Region in Eritrea: A Cross-Sectional Study

Abstract: Background Child marriage is a fundamental violation of human rights that can have numerous adverse effects on girls’ social, mental and physical health and wellbeing. Marriage in Eritrea relatively occurs earlier for women. This study aimed to assess the magnitude of child marriage, determinants and its related adverse health outcomes in five selected villages of the sub-region of Serejeka in Central region of Eritrea. Methods An analytical cross-sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Child marriage substantially affects women's experiences of pregnancy and childbirth and the health of the women and their offspring. Prolonged labor, abortion, hemorrhage during birth, spousal violence, pressure or stress, and termination of education were identified among women who get married early ( 6 8 ). Child marriage also has a negative attribution to cervical cancer and sexually transmitted infections (STIs) due to the inability to negotiate safer sex ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Child marriage substantially affects women's experiences of pregnancy and childbirth and the health of the women and their offspring. Prolonged labor, abortion, hemorrhage during birth, spousal violence, pressure or stress, and termination of education were identified among women who get married early ( 6 8 ). Child marriage also has a negative attribution to cervical cancer and sexually transmitted infections (STIs) due to the inability to negotiate safer sex ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the World Bank outlined that by 2030, four trillion dollars will be lost due to child marriage (2). Studies from different continents indicated that educational status, residence, income level, employment status, family size, knowledge about legal marital age, and parental decision-making about when to get married were the most important determinants of child marriage (8,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Girl child marriage, defined as the union of a girl under the age of 18, remains a critical, pervasive, and concerning global issue with far-reaching consequences for the physical, emotional, and social well-being of young girls. Several research reports indicated that girlchild marriage or early marriage is prevalent in almost all countries in the world and that this practice is a violation of human rights and has negative implications on the girl child (ICRW, 2006;UNICEF, 2012;Word Bank, 2014;Mehari et al, 2023). Again, UNICEF's (2019) report highlights the prevalence of child marriage globally.…”
Section: Introductionmentioning
confidence: 99%